In‐situ Synthesis of Stabilizer‐Free Gold Nanocrystals with Controllable Shape on Substrates as Highly Active Catalysts for Multiple Use. Issue 9 (15th February 2016) - Fu, Yanpeng; Lu, Yan; Polzer, Frank; Lux‐Steiner, Martha Ch.; Fischer, Christian‐Herbert
Abstract: Recyclable gold nanocatalysts with controllable morphology are in‐situ formed on the solid substrate by a facile ultrasonic spray pyrolysis method. The Au nanoparticles on Mo substrates form spheres, while on Si icosahedra, or after addition of Cu ions to the precursor solution, decahedra are obtained. The catalytic properties are studied for the reduction of 4‐nitrophenol as a model reaction and compared with those of several stabilized colloidal Au catalysts. Due to the absence of any stabilizers on the surface and the good adhesion to the solid support, the substrate‐immobilized Au nanoparticles exhibit excellent catalytic activity and stability as well as simple reuse without activity loss and easy recyclability. Furthermore, it is shown that by this spray pyrolysis process also the inner walls of a tube can easily be coated. The efficiency of this resulting flow‐through reactor is investigated. Finally, naked Au nanoparticle films enable a unique comparative investigation of the catalytic reaction rate in the presence of typical ligands used for the stabilization of colloidal nanoparticle catalysts. Only with the films of naked Au nanoparticles is a constant Au base available, while different ligands lead to different sizes and probably shapes of colloidal particles thus not allowing an exact comparison. It turns out that all investigated stabilizers reduce the catalytic efficiency. Abstract :